The impact of experienced stress on aged spatial discrimination: Cortical overreliance as a result of hippocampal impairment. Issue 3 (6th October 2015) - Marshall, Amanda C.; Cooper, Nicholas R.; Geeraert, Nicolas
ABSTRACT: A large body of neuroscientific work indicates that exposure to experienced stress causes damage to both cortical and hippocampal cells and results in impairments to cognitive abilities associated with these structures. Similarly, work within the domain of cognitive aging demonstrates that elderly participants who report experiencing greater amounts of stress show reduced levels of cognitive functioning. The present article attempted to combine both findings by collecting data from elderly and young participants who completed a spatial discrimination paradigm developed by Reagh and colleagues [Reagh et al. (2013 ) Hippocampus 24:303–314] to measure hippocampal‐mediated cognitive processes. In order to investigate the effect of stress on the cortex and, indirectly, the hippocampus, it paired the paradigm with electroencephalographic recordings of the theta frequency band, which is thought to reflect cortical/hippocampal interactions. Findings revealed that elderly participants with high levels of experienced stress performed significantly worse on target recognition and lure discrimination and demonstrated heightened levels of cortical theta synchronization compared with young and elderly low stress counterparts. Results therefore provided further evidence for the adverse effect of stress on cognitive aging and indicate that impaired behavioral performance among high stress elderly may coincide with an overreliance on cortical cognitive processing strategies as a result of early damage to the hippocampus. © 2015 Wiley Periodicals, Inc.